Total excision of a caudal mediastinal paraoesophageal abscess in a dog. Issue 1 (23rd January 2015) - Aisa, Josep; Grand, Jean‐Guillaume; Atencia, Sabela; Zarelli, Micaela; Callanan, John J
Abstract : A three‐year‐old female Irish setter dog presented with a history of shallow breathing, pyrexia and regurgitation. CT imaging revealed a 13×7×5 cm caudal mediastinal mass extending from the level of the right atrium to the diaphragm and surrounding the oesophagus. Total excision was achieved by a left sixth intercostal thoracotomy approach. Histological examination was consistent with a sterile abscess. The dog recovered uneventfully and was discharged on the third day after surgery. One year following surgery, the dog was in excellent physical condition with no evidence of recurrence of clinical signs. Total excision using a left sixth intercostal thoracotomy was a feasible and effective surgical option in this case. Benefit of total excision versus partial excision for caudal mediastinal paraoesophageal abscesses in dogs remains to be determined.